A wireless paging network with load-balancing equal opportunity routing in high-rise building construction - Guangxiang Yang; Hua Liang (International Journal of Distributed Sensor Networks, 2018)
The energy consumption of nodes is strictly limited in wireless sensor networks. The traditional direct delivery routing protocol is employed in the paging network of high-rise building construction elevators, which results in the high energy consumption and low successful delivery rate. A load-balancing equal opportunity routing protocol for wireless paging network is proposed in this work. The load-balancing equal opportunity routing protocol is a data transfer technique which maintains the network survivability by selecting the optimal path with both the lower energy consumption and the balanced network load. A load-balancing scheme gives equal opportunities for package transmission. A pager node delivers the packages by selecting a neighbor node with higher energy. The neighbor nodes in the coverage of the source node have an equal opportunity for routing. The sink node in the paging network broadcasts routing messages when moving along the track during the path selecting. The proposed load-balancing equal opportunity routing protocol is implemented and evaluated in a high-rise building construction elevator. The experimental results show that the average energy consumption of nodes is lowered with a balanced network load. It is estimated that successful delivery rate is increased by 55% but with a higher latency, and the network lifetime is prolonged.